Analysis of the statokinetic stability of track and field athletes with mental retardation in annual sports training cycles - Krasnoperova, T. V.; Lukmanova, N. B.; Bystrova, M. V.; Beleva, A. N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the statokinetic stability of athletes with mental retardation in a year-long sports training cycle using stabilometry.